Entitled or Excluded? Attitudes toward Access to Postsecondary Education for Undocumented Students - Courtney Palmer; Theresa Davidson (Arizona State University, 2011)
Abstract This study examines the determinants of attitudes towards undocumented immigrant studentsâ access to higher education, an area that has received little attention in the literature on immigration and public opinion. Theories of symbolic politics and labor market competition frame our research question. Using data from the 1994 General Social Survey, we find partial support for our predictions. Attitudes toward bilingual education, concerns about economic growth, and family income are significant predictors of public opinion regarding access to higher education for undocumented immigrants.